БАЛАНЫҢ РАЎАЖЛАНЫЎЫНА КОМПЬЮТЕР ТЕХНОЛОГИЯСЫНЫҢ ТӘСИРЛЕРИ - Кеўнимжаева, Г.П. (SCIENCE and SOCIETY, 2016)
The article focuses on the issues of impact of the computer on the health of children. The author considers the main points of interaction, child-computer, as well as violations of children’s health, caused by a long stay at the computer.